Three new species of Austrocarabodes (Oribatida: Carabodidae) from South Africa - Hugo, Elizabeth A. (Zootaxa, 2008)
Three new species of oribatid mites of the genus Austrocarabodes (Carabodidae), A. hendriksi sp. nov., A. vernoncrookensis sp. nov. and A. luciensis sp. nov. from various localities and biomes in South Africa are described. Comparisons are made between these new species and other known species.